Multi‐probe FISH Analysis of Immunophenotyped Chronic Lymphocytic Leukemia by Imaging Flow Cytometry. Issue 10 (5th October 2021) - Hui, Henry Y. L.; Stanley, Jason; Clarke, Kathryn; Erber, Wendy N.; Fuller, Kathryn A.
Abstract: Imaging flow cytometry is an automated method that enables cells and fluorescent signals to be visualized and quantified. Here, we describe a new imaging flow cytometry method whereby fluorescence in situ hybridization (FISH) is integrated with cell phenotyping. The method, called "immuno‐flowFISH, " provides an exciting new dimension for the analysis of genomic changes in cytological samples (e.g., blood, bone marrow). Cells are analyzed in suspension without any requirement for prior cell isolation or separation. Multiple antibodies and FISH probes, each with a unique fluorophore, can be added and many thousands of cells analyzed. Specific cell populations are identified by their antigenic profile and then analyzed for the presence of chromosomal defects. Immuno‐flowFISH was applied to the assessment of chronic lymphocytic leukemia (CLL), a mature B‐cell neoplasm where chromosomal abnormalities predict prognosis and treatment requirements. This integrated immunophenotyping and multi‐probe FISH strategy could detect both structural and numerical chromosomal changes involving chromosomes 12 and 17 in CLL cells. Given that many thousands of cells were analyzed and the leukemic cells were positively identified by their immunophenotype, this multi‐probe method adds precision to the cytogenomic analysis of CLL. © 2021 Wiley Periodicals LLC.